Spatial identification of traps in AlGaN/GaN heterostructures by the combination of lateral and vertical electrical stress measurements - Hu, Anqi; Yang, Xuelin; Cheng, Jianpeng; Lei Guo; Zhang, Jie; Ge, Weikun; Wang, Maojun; Xu, Fujun; Tang, Ning; Qin, Zhixin; Wang, Xinqiang; Shen, Bo (APPLIED PHYSICS LETTERS, 2016)
We present a methodology and the corresponding experimental results to identify the exact location of the traps that induce hot electron trapping in AlGaN/GaN heterostructures grown on Si substrates. The methodology is based on a combination of lateral and vertical electrical stress measurements employing three ohmic terminals on the test sample structure with different GaN buffer designs. By monitoring the evolution of the lateral current during lateral as well as vertical stress application, we investigate the trapping/detrapping behaviors of the hot electrons and identify that the traps correlated with current degradation are in fact located in the GaN buffer layers. The trap activation energies (0.38-0.39 eV and 0.57-0.59 eV) extracted from either lateral or vertical stress measurements are in good agreement with each other, also confirming the identification. By further comparing the trapping behaviors in two samples with different growth conditions of an unintentionally doped GaN layer, we conclude that the traps are most likely in the unintentionally doped GaN layer but of different origins. It is suggested that the 0.38-0.39 eV trap is related to residual carbon incorporation while the 0.57-0.59 eV trap is correlated with native defects or complexes. (C) 2016 AIP Publishing LLC.